Model Bimbingan Kelompok Berbasis Nilai Karakter Tokoh Kesultanan Palembang Darusalam untuk Siswa SMA - Sucipto, Sigit Dwi; Harlina, Harlina; Putri, Rani Mega (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
The aims of this study are: (1) to describe group guidance services and their implementation for high school students in Palembang City; and (2) produce a group guidance model based on the character values of the Palembang Darusalam sultanate figures for high school students in Palembang City. This study uses research and development (R & D) methods and designs with the following steps: (1) preliminary study and data collection; (2) research planning; (3) hypothetical model design; (4) validation of hypothetical models; (5)model revision; (6) final model. This study involved 2 guidance and counseling experts as expert validators and 5 guidance and counseling teachers as practitioner validators. Based on the results of the research and discussion, the conclusions of this study are: (1) Group guidance services for high school students in Palembang City are carried out discussing topics agreed upon when the implementation of group guidance has begun, and have not discussed the topic of the character values of Palembang figures, and (2) a group guidance model based on the character values of the Palembang Darussalam sultanate figures for high school students in thecity of Palembang. consists of 7 (seven) components, namely rationale, vision and mission, objectives, content of group counseling, support system, stages of group counseling, evaluation and follow-up.